The Use of Group Discussions to Improve the Achievement in Speaking Skill (e-Journal of Linguistics, 2020)
This is a pre- experimental research which usedone group pre- test and post-test design. The objectiveof this research was to know the effectiveness of groupdiscussion in improving the students’ English languagelearning using group discussion. The populations ofthis research were the ninth grade students of SMPN13 Maulafa Kupang numbering 233 students. Thesamples of this research were 35 students. Thevariables of the research were the students’achievement, as depend on variable, and the use ofgroup discussion as the independent variable. Themethod of collecting data used in this research was pre-test that was given before treatment and post-test thatwas given after treatment to analyzed the data, thewriter used t-test formula. the result of the researchshowed that the score of the t-test in the first sessionwas 11.15, while in the second session was 14. Thescore of t-table for level of significant for df 34 in level0.05 is 2.30 and in level 0.01 is 2.73. After comparingthe score of t-test and t-table, it means that groupdiscussion can significantly improve the students’achievement in English speaking ability. Besides, italso can make the class active, alive, and motivatestudent to work together to develop and share ideasmore freely. The problems that make the students weredifficult in speaking was the lack of vocabularymastery.
Keywords: Group Discussion; Speaking Ability; Independent variable